KARAKTERISTIK PENYELESAIAN TINDAK PIDANA SECARA INFORMAL MELALUI PERADILAN ADAT - Fitriati, Fitriati (Jurnal Media Hukum, 2017)
The legal inquiry is not just a matter of legal institutions and state organs, but also concerning the pursuit of justice that are informal. One of the problems of existing laws are criminal cases. Many criminal cases in village government were resolved through informal channels through a variety of methods are applied to each of the area. The process of settlement of criminal acts through the informal channels is a form of local wisdom in the law enforcement process. The research objective is to analyze the effectiveness of the settlement of criminal cases informally through customary justice. This study is a socio legal research. According to the research found that this form of criminal offense informal settlement is through village meetings, traditional justice, customary pemufakatan, direct action by the community for the provision of social sanction. Customary justice here is not justice terlembgaa as was common in formal law. The reason why the track in formal been is because it is considered more effective and efficient in terms of time, procedures and costs.